L-L multilevel boost converter topology for renewable energy applications: A new series voltage multiplier L-L converter of XY family - Bhaskar M.S.; Padmanaban S.; Fedak V.; Blaabjerg F.; Wheeler P.W.; Ramachandaramurthy V.K. (KoREMA, 2023)
A new L-L Multilevel Boost Converter (L-LMBC) topology for high gain renewable energy applications is proposed in this work. L-LMBC topology is designed to provide an operative solution for renewable energy applications which requires a high voltage conversion ratio and stack of the capacitor; such as a photovoltaic (PV) system with a Multilevel Inverter (MLI), electrical drives, automotive, hybrid electric cars etc. The proposed topology is derived by attaching the Cockcroft Walton (CW) multiplier to an upper L-converter of the LL topology of XY family. The mode of operation of L-LMBC with mathematical equations is also discussed in details. The noticeable features of proposed L-LMBC topology are: I) Only one power control switch; ii) High inverting output voltage from single input source; iii) Without the use of transformer; iv) The number of CW multiplier levels can be added to achieve high voltage without changing the connection of main circuits. The Matrix Laboratory (MATLAB) simulation results are provided and the result validates the functionality, feasibility and design of the converter. 2017 IEEE.